Harnessing University-Industry Collaboration in Malaysia through Industrial Training - Syahrul Nizam, Junaini; Sy F., Seyed Fadzir; Jonathan, Sidi; Mohd J., Ahmad Khiri; Rosita, Mohamed Othman (IEEE Xplore, 2014)
As Malaysia is rapidly growing in terms of the advancement of science and technology, unprecedented demand for better graduates has been created. However, industry often criticizes that existing university curricula fall short to tackle the practical issues in the industry. For instance, the industry expects the university to train their future employees with the latest technology. In this paper, we propose a smart synergy model to overcome the above-mentioned mismatch. Our hypothesis is that there are the needs for well-expressed and smart connectivity between academia and the industry. This paper highlights strategies to abolish the misalignment between university and industry. Our main concept is to blend the academic rigidity with the industrial relevance. First we analyzed the trend of university-industry partnership in Malaysia. We report the success story and issues behind the industrial training program at the Faculty of Computer Science and Information Technology, University Malaysia Sarawak.